Physico-Chemical Properties of Selected Cassava Varieties Suitable for Fufu Processing in South-East Abia Nigeria, Nigeria - Ugo, Chijioke (International Journal of Food Sciences, 2025)
Purpose: The physicochemical properties of cassava varieties have a major influence on the adoption and utilization for fufu processing and consumption across different locations in Nigeria especially the South-East region. This study evaluated the chemical composition, functional, and pasting properties of thirteen cassava (Manihot esculenta Crantz) varieties, including improved and farmer-preferred local varieties, to determine their suitability for fufu production in Abia State, Nigeria. Methodology: These physicochemical properties were determined using standard analytical procedures. The data collected were analysised using R- statistical package. Findings: The result obtained showed that the dry matter content of all the varieties ranged between 30% (NR8082) to 48.37% (the local clone). Starch content varied significantly, ranging from 47.46% to 61.20%, while total sugar ranged from 2.85% to 4.72%. Amylose and amylopectin contents indicated that most varieties could be classified as regular starch types, with desirable amylose-to-amylopectin ratios for fufu processing. The result of functional properties such as swelling power (9.12–14.99 g/g), solubility, and water absorption capacity also indicate these varieties are suitable for fufu processing. Pasting characteristics, including peak, final, and setback viscosities, revealed varietal suitability for specific textural and sensory attributes of fufu. Unique Contribution to Theory, Practice and Policy: Overall, several improved cassava varieties exhibited comparable or superior quality traits relative to the local variety, suggesting their potential for adoption by processors and consumers seeking desirable fufu qualities.